Developing electronic animated media to help elementary school students understand motion prepositions - Lusia Eni Puspandari (UPT P2M Politeknik Negeri Malang, 2014)
This paper is directed to find out an alternative way for students of Elementary School in understanding motion prepositions. The result of this study is in form of courseware which is directed to overcome learners’ difficulties in understanding and using motion prepositions. This study is used as an adjunct to English learning processes and this courseware can be accessed every time in indefinite pace as self-learning media based on the learners’ own ability. In developing attractive learning media, the concept of independent learning and instructional animation are the basis of the study. It is supported by some components namely: attention-gaining material, pretest/posttest, instructional objectives, tutorial, content, exercises, and feedback. The result of the try out shows that most of the students become more understand the uses and the differences of the motion prepositions in sentences.